Interpreting ‘bulugh’: enhancement of women’s right through management of marriage within salafi community in Wirokerten Yogyakarta - Fatum Abubakar; Euis Nurlaelawati; Ahmad Bunyan Wahib (Indonesian Journal of Islam and Muslim Societies, 2022)
This article discusses Salafi Wirokerten women and the enhancement of their status and rights through management of marriage and interpretation of bulugh (legal maturity for marriage). It therefore observes the practice of marriage within Salafi women in term of age and their attitudes toward their own manhaj. It also seeks to see the Salafi’s attitude in general toward the state law of marriage. The materials of this article were obtained from ethnographic investigation that was conducted in a Wirokerten village in Banguntapan sub-district of Yogyakarta in 2018-2019 through interviews, participatory observations, group discussions. Deploying anthropological approach this article finds that Salafi women have notions to improve their rights, and they stress the importance of the maturity of religious knowledge. This article also argues that Salafi women identify themselves as Salafi agents by transforming authority to gain manhaj recognition of marital management as a source of strength and empowerment. In addition, it concludes that Salafi women have an important role in bridging relations of the Salafi manhaj with the state and that while negotiating state law with their own manhaj, they often need to refer to Islamic doctrines to base and strengthen their position. They refer not only to Islamic teachings but also propagate narratives of the significance of study and of being knowledgeable to do and thus to marry.